Pengaruh Sikap Religius Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Transco Dharmasraya - Bayu Pratama Azka; Robby Dharma; Tito (Riset Sinergi Indonesia, 2022)
This study aims to examine the effect of religious attitudes, leadership styles, on employee performance through job satisfaction at PT Transco Dharmasraya. The method of collecting data is through surveys and distributing questionnaires, with a sample of 90 respondents. The data analysis method used is path analysis using computer assistance with the SPSS version of the software program is 21. The results obtained based on the t test (partial test) obtainedPartially Religious Attitude (X1) has a significant effect on Job Satisfaction (Z), Partially Leadership Style (X2) has no significant effect on Job Satisfaction, Partially Religious Attitude (X1) has a significant effect on Employee Performance (Y), Partially Leadership Style (X2) has an insignificant effect on employee performance (Y), partially job satisfaction (Z) has a significant effect on employee performance (Y), the direct influence of religious attitudes (X1) is greater than the indirect influence of religious attitudes (X1) on Employee Performance (Y) through Job Satisfaction (Z), The direct influence of Leadership Style (X2) is greater than the indirect influence of Leadership Style (X2) on Employee Performance (Y) through Job Satisfaction (Z), Contribution of the independent variable contribution Attitude Religion (X1) and Leadership Style (X2) on the dependent variable Job Satisfaction (Z), the contribution of the independent variable Religious Attitude (X1 ), Leadership Style (X2) and Job Satisfaction (Z) on the dependent variable Employee Performance (Y).